Perceptions of body weight that vary by body mass index: Clear associations with perceptions based on personal control and responsibility. (January 2022) - Robinson, Karen; Muir, Sarah; Newbury, Annie; Santos-Merx, Lourdes; Appleton, Katherine M
This project aimed to identify the perceptions of body weight that vary by body mass index. First, a qualitative study explored body weight perceptions in 17 individuals with overweight. Second, a questionnaire was developed and completed by a UK sample with body mass index from 16.6 to 59.7 kg/m 2 ( N  = 328). A higher body mass index was associated with perceptions of less personal control and responsibility. Body mass index in females was also associated with three other questionnaire factors and body mass index in males with illness/medication. Thus, body mass index was associated with different perceptions of body weight. Focussing on personal control and responsibility may be useful for treatment and prevention.